2009
DOI: 10.1111/j.1460-9568.2009.06669.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in alternative brain‐derived neurotrophic factor transcript expression in the developing human prefrontal cortex

Abstract: In this study, we determined when and through which promoter brain-derived neurotrophic factor (BDNF) transcription is regulated during the protracted period of human frontal cortex development. Using quantitative real-time polymerase chain reaction, we examined the expression of the four most abundant alternative 5' exons of the BDNF gene (exons I, II, IV, and VI) in RNA extracted from the prefrontal cortex. We found that expression of transcripts I-IX and VI-IX was highest during infancy, whereas that of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 47 publications
4
47
0
1
Order By: Relevance
“…10,14,20,59 Likewise, it may be that the blood levels of BDNF in the periphery reflect the brain levels as has been shown in the development and aging of the rat. 60 Thus, measuring peripheral BDNF levels may provide a biomarker for disease state or provide a marker for treatment response.…”
Section: Discussionmentioning
confidence: 93%
“…10,14,20,59 Likewise, it may be that the blood levels of BDNF in the periphery reflect the brain levels as has been shown in the development and aging of the rat. 60 Thus, measuring peripheral BDNF levels may provide a biomarker for disease state or provide a marker for treatment response.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, a recent study suggests that a single CpG site could be a good proxy for the whole CpG Island to which the site belongs to in terms of methylation (Barrera and Peinado, 2012). The different promoters located at the 5 side of the BDNF gene combined with different splice sites and the presence of an antisense regulatory mechanism are thought to be responsible for the production of different transcript isoforms of BDNF that are differentially expressed among tissues and at various development periods (Wong et al, 2009). Previous work performed in mice showed that promoter IV was active in nonneural tissues (lung, heart, and muscle), whereas promoters I, II, and III were predominantly used in the brain (Timmusk et al, 1993(Timmusk et al, , 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Four 'housekeeper' genes that did not change expression with development were chosen: hydroxymethylbilane synthase (Hs00609297_m1), glucuronidase-b (Hs99999908_m1), ubiquitin C (Hs00824723_m1) and cyclophilin A (Hs99999904_m1). 63 Serial dilutions of pooled cDNA (from seven samples, one from each developmental time point) were included on every qPCR plate for quantification of sample expression by the relative standard curve method. Efficiencies of the qPCR reactions ranged from 77-100%, with R 2 values ranging between 0.95 and 1.00.…”
Section: Tissue Collectionmentioning
confidence: 99%